EXPLORING THE MILLENNIALS PREFERENCES IN MOISTURIZER PRODUCT USING MIX METHOD APPROACH - Jannah, Hannifah Miftakhul; Hakim, Muhammad Saiful; Hakim, Nabila Silmina (Jurnal Mebis, 2023)
In recent years, we have witnessed the growing interest from millennials to preserve their skin health. In order to maintain their skin health, they consume a variety of skincare products. One of the essential products for them is moisturizer product. This research objective is to explore the critical moisturizer product features for customer purchase decision. This research employs mixed method that consists of descriptive study and interview to millennials. The result of descriptive study indicates that price of the product is important cue for quality, therefore, consumer is preferring to select product with middle range prices. Descriptive analysis also reveals that consumer has weighted their decision based on the product composition and product efficacy. In addition, the analysis shows that consumer prefer small size product so it will be more practical to keep in carry on container. The interview gives us detailed information regarding the purchase decision process. The analysis of interview uncovers that beauty vlogger with honest review is more credible for purchase behavior compared with well-known brand ambassadors.